Prevalencia y severidad de caries dental e higiene bucal en niños y adolescentes de aldeas infantiles, Lima, Perú - Mattos-Vela, Manuel Antonio (2017)
Abstract: Objective: To determine the prevalence and severity of dental decay and oral hygiene in children and adolescents in Children’s Villages of Lima. Materials and methods: Transversal descriptive study. A non-random sample of 224 children aged 1 to 17 who resided in one of three SOS Children's Villages participated in the study. Dental decay was evaluated with the WHO diagnostic criteria, and oral hygiene was measured with the Greene and Vermillion Debris Index. Results: The prevalence of dental decay in the group aged 1-4 was 36.8%, and in the 5-7, 11-13 and 14-17 groups, the prevalence was 67.7%, 56.6% and 82.4%, respectively, considering both dentitions. Caries severity (dmft+DMFT) in the same groups had an average ± standard deviation of 1.16±2.41, 3.48±3.71, 1.66±2.02 and 3.19±2.51, respectively. Fair oral hygiene was predominant in the sample, with a prevalence above 50% in all age groups, with the exception of the 14 to 17 age group, where hygiene proved to be more frequent (67.2%). Conclusions: Results show a significantly high prevalence of dental decay alongside poor oral hygiene, proving that it is necessary to implement oral health programs for at-risk populations.